(untitled) (Revista de Crítica Literaria Latinoamericana, 2014)
This essay proposes an ecocritical approach to Latin American literature of the early modern/colonial era based on a three-part conceptualization of subjectivity: identities, epistemologies, and corporalities. It offers a summary of recent research on “nature” in colonial studies and advocates for a hybrid methodology that incorporates aspects of phenomenology in an attempt to register the progressive emergence of Cartesian subjectivity.